TRANSCRANIAL MAGNETIC STIMULATION IN POST-STROKE RECOVERY - A REVIEW - Julia Błocka,; Agata Lurka,; Agata Panfil,; Monika Banaszek,; Hanna Pietruszewska,; Daria Godlewska,; Julia Rarok,; Natalia Senatorska,; Agnieszka Pruska,; Katarzyna Kleszczewska, (International Journal of Innovative Technologies in Social Science, 2025)
Stroke remains a leading cause of long-term disability worldwide, underscoring the urgent need for effective neurorehabilitative strategies to restore function and independence. This review synthesizes current evidence on the role of transcranial magnetic stimulation (TMS) in post-stroke recovery across motor, cognitive, linguistic, and affective domains. We first outline the pathophysiological basis of post-stroke cortical imbalance - characterized by disrupted excitatory-inhibitory dynamics and maladaptive interhemispheric inhibition and the mechanistic principles through which TMS modulates cortical excitability and promotes neuroplasticity. Drawing on recent clinical studies and meta-analyses, we evaluate the therapeutic efficacy of TMS in enhancing recovery. Evidence indicates that stimulation can improve motor function, mood, language, and cognition. Optimal outcomes are observed when TMS is applied within the subacute phase and combined with task-specific training, speech-language therapy or cognitive rehabilitation, reflecting synergistic effects on experience-dependent plasticity. TMS is generally well-tolerated, with adverse effects limited to transient scalp discomfort or headache when administered within established safety guidelines. Despite encouraging results, variability in stimulation parameters, patient selection and lesion characteristics limits standardization. Future directions emphasize personalized, biomarker-guided protocols and large multicenter trials to refine treatment optimization. Overall, TMS represents a promising, mechanism-based adjunct to conventional rehabilitation, capable of re-engaging neuroplastic processes and enhancing functional recovery after stroke.